Evaluasi Hasil Preparasi Servikal pada Model Kerja Gigi Tiruan Jembatan - Fransiska Nuning; Poetry Oktanauli; Herjanti Tyawati (Majalah Kedokteran Gigi Indonesia, 2014)
Evaluation of Cervical Working Model Bridge Preparation. The accuracy of the cervical edge preparation is the most important element in evaluating a restoration. Good restoration results obtained from accurate impression with cervical corresponding side. A restoration was successful to survive in the oral cavity if it can adapt to the cervical edge surface preparation line side. The study was conducted on 57 patients of the students who are doing work in clinics Prosthodontics. Research criteria are appropriate and not appropriate based on previous research that gets results of the evaluation as much as 70% on the operating model. The results showed the assessment of cervical preparation in proper working model that included as many as 78,95%.